18 Dosimetric study of the couch top influence in VMAT. (December 2018) - Dimitriadi, E.; Leni, P.E.; Gschwind, R.; Grosperrin, C.; Vasseur, A.
Abstract : Introduction: During these last years, treatment planning system (TPS) algorithms that compute the absorbed dose have improved. A high precision between delivered absorbed dose and prescribed dose is required, limiting the uncertainties up to 5% between delivered dose and prescribed dose according to the ICRU recommendations[1] . One of the parameters contributing to these uncertainties is the couch top, which attenuates the beam from 2% to 15% when it passes through[2] . Last generation's carbon fiber couch tops act as a bolus material, increasing skin dose while decreasing depth-dose. Therefore, the consideration of the couch top by the TPS is important for avoiding bad tumor control, overdose of organs at risk and skin radiotoxicity effects[2] . Methods: The reference technique for the dose distribution calculations is based on Monte Carlo method (MC)[3] . Among the most well-known codes, BEAMnrc/EGSnrc allows to model the accelerator treatment head and to use CT images (DICOM format) in order to simulate the dose distribution to voxelized phantoms. Furthermore, the CT data have to be converted to densities and to the corresponding materials, taking into account the couch top[4] . A software developed by the team using a conversion ramp between Hounsfield Units (HU) and densities/materials, specific to the couch top, will be used to create the voxelized phantoms. Results: MC method takes into consideration not only voxel densities, but also materials, if a wrong material assignment is made, it could lead to dosimetric errors in the dose distribution calculations. Different treatment sites will be considered in Volumetric Modulated Arc Therapy (VMAT). Phantoms with the couch top will be created and dose distributions will be compared to TPS dose distributions. Conclusions: The results of this study contributed to evaluate different methods of taking into account the couch top, using MC.